Stillbirth: Knowledge and Practice among U.S. Obstetrician-Gynecologists - Goldenberg, Robert L.; Farrow, Victoria; McClure, Elizabeth M.; Reddy, Uma M.; Fretts, Ruth C.; Schulkin, Jay (American Journal of Perinatology, 2013)
Objective To determine knowledge of U.S. obstetrician-gynecologists (OBGYNs) and individual and institutional practices regarding stillbirth.Study Design We surveyed 1,000 members of the American College of Obstetricians and Gynecologists regarding their knowledge of risk factors and causes of stillbirth and self-rated performance in stillbirth management.Results Of the 499 who responded, 365 currently practiced obstetrics. Knowledge regarding epidemiology, risk factors, and effective interventions to reduce stillbirth was only fair. About 30% of respondents were unaware that preeclampsia, advanced maternal age, elevated α-fetoprotein, multiple gestation, cigarette smoking, illicit drug use, and being postterm increased risk. Tests to identify stillbirth causes were not performed consistently. Forty-two percent of respondents did not review test results to determine cause. Most hospitals did not have protocols for stillbirth evaluation nor preprinted forms to obtain appropriate stillbirth tests. Stillbirth audits with feedback were rarely performed.Conclusions OBGYN knowledge and institutional practice regarding stillbirth could be substantially improved. Residency programs need improved education regarding stillbirth. Hospitals and their OBGYN departments should focus more on stillbirth through continuing education programs and grand rounds and develop stillbirth management protocols and standardized order sheets to appropriately evaluate stillbirths. Audits that evaluate cause of death and preventability with a feedback loop focused on improvement in care should be considered.
Keywords: stillbirth; fetal death; obstetric practice; OBGYN knowledge